Periodic Solution of the Hematopoiesis Equation - Ji-Huan He (Abstract and Applied Analysis)
Wu and Liu (2012) presented some results for the existence and uniqueness of the periodic solutions for the hematopoiesis model. This paper gives a simple approach to find an approximate period of the model.